4D printing of liquid crystal emulsions for smart structures with multiple functionalities - Concellón, Alberto; Mainik, Philipp; Vázquez-Martel, Clara; Álvarez-Solana, Cristina; Blasco, Eva (Angewandte Chemie. International edition, 2025)
3D printing, and more recently 4D printing, has emerged as a transformative technology for fabricating structures with complex geometries and responsive properties. However, employing functional colloidal solutions as inks for printing remains unexplored. In this work, we present a novel and versatile 4D printing approach for fabricating functional and complex-shaped objects using polymerizable liquid crystal (LC) emulsion droplets. Leveraging a digital light processing (DLP) 3D printing technique, we achieve rapid production of intricate 3D geometries with high resolution. The printed structures retain the LC ordering from the precursor droplets, imparting the final objects with shape memory properties, including shape fixation and recovery upon heating or light exposure. Light-responsive behavior is introduced post-printing by embedding an azo dye into the 3D structures. Additionally, we explore the potential to create intrinsically porous 3D structures by selectively removing non-reactive components from the printed geometries, adding an extra level of functionality to the printed objects. Furthermore, we incorporate chiral nematic LCs into the emulsion droplets, producing 3D objects with tunable reflective properties. To our knowledge, this is the first example of DLP 3D printing with emulsions, offering an effective and versatile pathway for developing 4D-printed materials with potential applications in optics, robotics, microfluidics, and biomedicine.